2016
DOI: 10.1007/s13364-016-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation of predator diet in a rural habitat: stone martens in the villages of Białowieża forest

Abstract: The seasonal and spatial variation of the stone marten's (Martes foina) diet was studied in the villages of Białowieża Forest, north-eastern Poland. Stone marten diet varied significantly among seasons, years and villages of different size. The most important food sources were fruits and birds: 41.5 and 32.9 % of consumed biomass (% Bio), respectively. From summer to winter, fruits were the most important food, in contrast to spring, where birds dominated the diet followed by small mammals, fruits and other pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(78 reference statements)
1
10
1
Order By: Relevance
“…This was confirmed by clustering methods implemented in STRUCTURE, TESS and DAPC. Greater structures in stone marten populations, with higher probabilities of assignment to groups have been observed elsewhere in Europe (France, Portugal and Spain); however the geographic areas considered in these studies were slightly larger than in our study [ 78 81 ]. A weak genetic structure for the stone marten population in Poland seems to confirm the absence of ecological barrier-restricted dispersal.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…This was confirmed by clustering methods implemented in STRUCTURE, TESS and DAPC. Greater structures in stone marten populations, with higher probabilities of assignment to groups have been observed elsewhere in Europe (France, Portugal and Spain); however the geographic areas considered in these studies were slightly larger than in our study [ 78 81 ]. A weak genetic structure for the stone marten population in Poland seems to confirm the absence of ecological barrier-restricted dispersal.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition, its less arboreal lifestyle compared to pine marten exposes it to an increase risk of predation in forests, when moving or resting on or under the ground [ 22 ]. Furthermore, villages, in contrast to forests, offer a high abundance of food throughout the year [ 78 ]. The genetic analyses in this study show, for the first time, that a large forest complex is not only a habitat that is avoided by stone marten but also constitutes an environmental barrier in the dispersal of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Fleshy fruits with high levels of carbohydrate, minerals and vitamins but low pro-LANSZKI, ZS., PURGER, J. J., BOCZ, R., SZÉP, D. & LANSZKI, J. tein contents (Pandolfi et al 1996, Jordano 2000 are consumed in winter, as confirmed by numerous other studies too (e.g. Rasmussen & Madsen 1985, Tester 1986, Tóth 1998, Bermejo & Guitian 2000, Lanszki 2003, Bakaloudis et al 2012, Georgiev 2013, Czernik et al 2016, Petrov et al 2016. Winter was mild at the time of the investigations, thus the fruits having remained in the area stayed available for quite long.…”
Section: Discussionmentioning
confidence: 59%
“…Samples were collected along a total of 4.28 km long standard route on the top of the stone walls separating vineyard plots, and along the road network running through the vineyard, and were distinguished based on odour, size and shape characteristics (Macdonald 1980). Due to the regular human presence in the area associated with viticulture, the presence of the forest-preferring pine marten (Martes martes) in the area is considered to be only occasional even despite the proximity of forests, as suggested by experience from radio telemetry studies (Zalewski 1997, Czernik et al 2016, meaning that the majority of the collected samples possibly originated from stone martens. No other canid species (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…These factors may also vary seasonally and can be related to habitat characteristics (e.g. Day et al, 2015;Czernik et al, 2016). In case of an opportunistic foraging strategy, diet composition simply reflects present prey availability.…”
Section: Introductionmentioning
confidence: 99%